2013
DOI: 10.1111/tbj.12105
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Breast Cancer Following Breast Conserving Surgery

Abstract: Patients with isolated ipsilateral breast cancer recurrence face completion mastectomy in the majority of cases. Selected patients may derive good outcomes from repeat breast conservation surgery and indeed repeat irradiation may be employed using one of many different modalities. Tumor biology rather than salvage surgery method is likely to influence outcome. Patients with isolated breast tumor recurrence are treated in the majority of cases with completion mastectomy, when for selected patients there exists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The study demonstrated that patients who received repeat lumpectomy plus RT achieved comparable 5‐ and 10‐year DFS and OS to those who underwent a mastectomy. It is commonly accepted that a second full‐dose course of whole breast radiotherapy therapy after repeat lumpectomy cannot be tolerated by the tissues and would lead to unacceptable levels of toxicities and poor cosmetic result . However, several published articles demonstrate that accelerated partial breast irradiation after repeat lumpectomy is safe and feasible and can achieve acceptable skin, fibrosis, and breast pain toxicity, as well as satisfactory cosmetic results .…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that patients who received repeat lumpectomy plus RT achieved comparable 5‐ and 10‐year DFS and OS to those who underwent a mastectomy. It is commonly accepted that a second full‐dose course of whole breast radiotherapy therapy after repeat lumpectomy cannot be tolerated by the tissues and would lead to unacceptable levels of toxicities and poor cosmetic result . However, several published articles demonstrate that accelerated partial breast irradiation after repeat lumpectomy is safe and feasible and can achieve acceptable skin, fibrosis, and breast pain toxicity, as well as satisfactory cosmetic results .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these patients present with bulky, large volume disease, further complicating management. Hyperthermia has emerged as a useful adjunct treatment that can improve the radiosensitivity of cancer cells, thus achieving greater tumor control with lower doses of radiation compared to radiation alone [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Before 1990, the CMU program (colchicine, methotrexate, and uramustine) was widely used; since 1990, CEF (cyclophosphamide, doxorubicin/epirubicin, and fluorouracil), CMF (cyclophosphamide, methotrexate, and fluorouracil), or TE (taxane and anthracyclines) has been used. Anthracyclines, such as doxorubicin or epirubicin, decrease the annual cancer recurrence risk by 2% and death risk by 11%, and further decrease the absolute benefit by 3.2% and 2.7%, respectively (Litière et al, 2012;Burger et al, 2013). Taxanes, such as paclitaxel and docetaxel, are suitable for patients with positive lymph nodes.…”
Section: A Brief Literature Review Of Male Accessory Breast Cancermentioning
confidence: 99%